Fringing field can prevent infinite time quenching. (August 2016) - Pan, Hongjing; Xing, Ruixiang
Abstract: Consider the following problem arising in Micro-Electro-Mechanical Systems (MEMS) u t − Δ u = λ ( 1 + δ ∣ ∇ u ∣ 2 ) ( 1 − u ) p, ( x, t ) ∈ Ω × ( 0, T )